Pengaruh Media Mind Mapping Dalam Layanan Bimbingan Konseling Terhadap Motivasi Belajar Dan Perencanaan Karir Siswa di SMPN 1 Tragah - Hartatik, Hartatik; Huda, Nuril; Purnamasari, Hetty (Peneliti.net, 2024)
The objectives of this research include: 1) To determine the influence of media mind mapping in guidance and counseling services on the learning motivation of class IX students at SMPN 1 Tragah, and 2) to determine the influence of media mind mapping in guidance and counseling services on career planning for students of class IX SMPN 1 Tragah. This research uses a quantitative approach and is an experimental type of research with a Nonequivalent Control Group Design. The research samples were 30 students in class IX-A as the control class and 30 students in class IX-D as the experimental class. The data analysis technique uses the independent sample t test analysis technique. The research conclusions include: 1) There is an influence of media mind mapping in guidance and counseling services on the learning motivation of class IX students at SMPN 1 Tragah, and 2) there is an influence of media mind mapping in guidance and counseling services on career planning for students of class IX SMPN 1 Tragah.